Integrated Arts and Culture Education Model for Public Schools in Indonesia: The Case Study of 'Made in Cirebon' as a Cooperation Project with an Artist Community - Jeong Ok Jeon; Evelyn Huang; Nin Djani (Journal of Visual Art and Design, 2022)
There is an urgency to improve arts and culture education in public schools in Indonesia. Currently, the sector faces various challenges, such as insufficient course hours, limited topics, as well as inadequate number and expertise of teachers. With the Covid-19 pandemic, the situation has become even more precarious. To solve these problems, ARCOLABS organized an alternative arts and culture education program for local public-school students in 2020 as part of the Official Development Assistance (ODA) for Arts and Culture Education. Entitled ‘Made in Cirebon’, this pilot project served as preliminary research to look for the most appropriate models to encourage innovations and sustainability in arts and culture education in local public schools in Cirebon through cooperation with local artists. This project-based study utilized several research methodologies, including seminars and discussions to develop learning contents, implementation of an online/on-site learning model, a mini showcase of learning outcomes by students, along with participant interviews, surveys, and evaluation by all stakeholders to prepare for a successive project in 2021. Through the inclusive, innovative and productive outcomes of the project, this research has drawn several positive conclusions: (1) various genres and disciplines can be integrated into an interdisciplinary subject that could overcome the limited course hours and topics within the school curriculum; (2) local artists can be important artistic and educational assets that could fill the gaps in formal education; and (3) a creative approach to local issues is a significant catalyst for the sustainability of the implemented model.